Spatial Distribution of Trace Elements in Rice Field at Prafi District Manokwari - Aplena Elen S. Bless; Samen Baan; Yahya Darmawan (Indonesian Journal of Geography, 2016)
Mapping spatial variability of trace elements in rice Ḁeld is necessary to obtain soil quality information to en-hance rice production. ἀis study was aimed to measure concentration and distribution of Zn, Cu, Fe, Pb, and Cd in two diᴀerent sites (SP1, SP2) of PraḀ rice Ḁeld in Manokwari West Papua. ἀe representative 26 soil samples were analysed for their available trace metal concentration (DTPA), soil pH, and C-organic and soil texture. ἀe result indicated that Fe toxicity and Zn deḀcient problems were encountered in both sites.  Rice Ḁeld in SP2 was more deḀcient in Zn than SP1. Site with the highest trace elements (Zn, Fe, Cu, and Cd) concentration had low soil pH and high C-organic. Acidic soil has higher solubility of metals; while high C-organic could improve the formation of dissolve organic carbon-metal binding, hence it improving the trace metals concentration in soil solution.